2007
DOI: 10.1111/j.1748-1716.2006.01663.x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the brain renin–angiotensin system in rats with chronic renal failure

Abstract: The brain renin-angiotensin system in subtotally nephrectomized SHR appears to be activated via afferent nerves from the remnant kidney, resulting in sympathetic overactivity and hypertension in this chronic renal failure model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
2
11
0
1
Order By: Relevance
“…Expression of the intrarenal angiotensinogen and renin was suppressed and ACE expression was unchanged in Mdk +/+ mice, which was consistent with previous findings after 5/6 nephrectomy of rats (19,20) (Supplemental Figure 2, A-C). In contrast to the kidney, the lung showed significant increases in ACE expression and its activity 2 and 4 weeks after renal ablation (Figure 2, A-E).…”
Section: Figuresupporting
confidence: 81%
See 1 more Smart Citation
“…Expression of the intrarenal angiotensinogen and renin was suppressed and ACE expression was unchanged in Mdk +/+ mice, which was consistent with previous findings after 5/6 nephrectomy of rats (19,20) (Supplemental Figure 2, A-C). In contrast to the kidney, the lung showed significant increases in ACE expression and its activity 2 and 4 weeks after renal ablation (Figure 2, A-E).…”
Section: Figuresupporting
confidence: 81%
“…CKD has also been linked with damage in other organs, especially with cardiovascular damage (so-called cardiorenal syndrome) (30). It is particularly interesting that RAS components are increased in the heart and brain of subtotally nephrectomized rats (20,31) and that Ang II amounts are increased in the isolated perfused hind limbs of uremic rats (32). Inhibitors of the RAS, e.g., angiotensin receptor blockers and ACE inhibitors, are indeed the first choice of therapy for CKD (33).…”
Section: Discussionmentioning
confidence: 99%
“…39,43,44 Furthermore, the brain renin-angiotensin system was upregulated in rats with chronic renal failure. 45 Therefore, the renin-angiotensin system in the brain may stimulate the generation of central oxidative stress associated with renal dysfunction. Moreover, brain aldosterone and mineralocorticoid receptors, which are stimulated by the renin-angiotensin system, can also be involved in central oxidative stress-induced sympathoexcitation.…”
Section: Fujita Et Al Sympathoexcitation Via Brain Ros In Ckd 109mentioning
confidence: 99%
“…9 It has also been reported that ARNs are connected to the central areas, including the nucleus tractus solitarius, the paraventricular nucleus, the supraoptic nucleus, the subfornical organ and others. 26,27 In the present study, ICV injection of an Ang II AT1 receptor antagonist, CV-11974, significantly attenuated the increases in RSNA and blood pressure in response to elevation of pelvic pressure. Collectively, these findings support the hypothesis that afferent nervous information from the kidney is transmitted to the CNS and stimulates the systemic sympathetic activity via the CNS RAS-mediated pathways.…”
Section: Wky Rats Shrsmentioning
confidence: 91%